THE ROLE OF EMOTIONAL INTELLIGENCE IN TEACHER-STUDENT RELATIONSHIPS AND ITS IMPACT ON LEARNING OUTCOMES ("Conference on Universal Science Research 2023", 2024)
This study explores the complex relationship between emotional intelligence (EI) and how it affects academic performance and teacher-student interactions. In order to promote constructive interactions in the classroom, emotional intelligence—which includes self-awareness, self-regulation, social awareness, and relationship management—is seen to be essential. The study investigates how the emotional intelligence of instructors affects the caliber of their interactions with students and, in turn, how well the kids perform academically. This work aims to further knowledge of the complex relationships among emotional intelligence, interpersonal relationships, and academic performance by an extensive examination of the body of current literature, empirical research, and case studies.